Resistance or compliance? The impact of algorithmic awareness on people's attitudes toward online information browsing - Yuan, Ying; Shi, Yin; Su, Ti; Zhang, HanXuan (Frontiers in Psychology, 2025)
IntroductionWith the pervasive integration of big data algorithms into daily life, individuals increasingly rely on algorithmic filtering to access information of interest, yet simultaneously face the risk of confinement within “information cocoons.” This study examines how algorithmic awareness influences people's attitudes toward online information browsing.MethodsUsing a 2 × 2 mixed design (algorithmic awareness × browsing purpose), this study reveals the mediating roles of perceived power and internal control. Participants performed simulated information-seeking tasks where all content was randomly presented (eliminating actual algorithmic bias). Mediating roles of perceived power and internal control were analyzed using PROCESS macro.ResultsAlgorithmic awareness significantly increases people's compliance, especially when they browse online information with a certain purpose, despite all information in the experiment being presented randomly. Algorithmic awareness increases people's sense of power and internal control over information, which, in turn, increases algorithmic compliance behavior.DiscussionResults reveal that algorithmic awareness reshapes user behavior through psychological empowerment, even in algorithm-neutral environments. By studying the influencing factors of mobile new media users' compliance and resistance to algorithms, this study is helpful in assisting users to eliminate their state of technological unconsciousness and achieve good algorithmic use.